Reaction of N-Acetylcysteine with Cu2+: Appearance of Intermediates with High Free Radical Scavenging Activity: Implications for Anti-/Pro-Oxidant Properties of Thiols - Valent, Ivan; Bednárová, Lucie; Schreiber, Igor; Bujdák, Juraj; Valachová, Katarína; Šoltés, Ladislav (International journal of molecular sciences, 2022)
We studied the kinetics of the reaction of N-acetyl-l-cysteine (NAC or RSH) with cupric ions at an equimolar ratio of the reactants in aqueous acid solution (pH 1.4−2) using UV/Vis absorption and circular dichroism (CD) spectroscopies. Cu2+ showed a strong catalytic effect on the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) radical (ABTSr) consumption and autoxidation of NAC. Difference spectra revealed the formation of intermediates with absorption maxima at 233 and 302 nm (ε302/Cu > 8 × 103 M−1 cm−1) and two positive Cotton effects centered at 284 and 302 nm. These intermediates accumulate during the first, O2-independent, phase of the NAC autoxidation. The autocatalytic production of another chiral intermediate, characterized by two positive Cotton effects at 280 and 333 nm and an intense negative one at 305 nm, was observed in the second reaction phase. The intermediates are rapidly oxidized by added ABTSr; otherwise, they are stable for hours in the reaction solution, undergoing a slow pH- and O2-dependent photosensitive decay. The kinetic and spectral data are consistent with proposed structures of the intermediates as disulfide-bridged dicopper(I) complexes of types cis-/trans-CuI2(RS)2(RSSR) and CuI2(RSSR)2. The electronic transitions observed in the UV/Vis and CD spectra are tentatively attributed to Cu(I) → disulfide charge transfer with an interaction of the transition dipole moments (exciton coupling). The catalytic activity of the intermediates as potential O2 activators via Cu(II) peroxo-complexes is discussed. A mechanism for autocatalytic oxidation of Cu(I)−thiolates promoted by a growing electronically coupled −[CuI2(RSSR)]n− polymer is suggested. The obtained results are in line with other reported observations regarding copper-catalyzed autoxidation of thiols and provide new insight into these complicated, not yet fully understood systems. The proposed hypotheses point to the importance of the Cu(I)−disulfide interaction, which may have a profound impact on biological systems.
Keywords: circular dichroism; antioxidancia; sulfhydrylové sloučeniny; Acetylcysteine; Copper; Oxygen; autoxidation; reaktivní formy kyslíku; acetylcystein; disulfide; exciton coupling; dioxygen activation; Disulfides; copper catalysis; oxidace-redukce; Reactive Oxygen Species; kyslík; Sulfhydryl Compounds; Antioxidants; měď; disulfidy; Oxidation-Reduction; dicopper complex